Boosting Wellness through Books: Reading Culture and Library Usage among Students at Lagos State University - Abiodun-Asanre, Oluwaseun Adeola; Azeez, Rasheed Olawale; Bokoh, Mausi Ajoviyon (Communicate: Journal of Library and Information Science, 2024)
This study examined the effect of reading culture and library usage on the wellness of students at Lagos State University. Using the descriptive survey research design and the convenience sampling technique, 1313students were selected as respondents for this study. Three hypotheses were stated and tested using the Pearson Product Moment correlation coefficient (PPMC) and multiple regression. Findings from hypothesis oneshows a positive and statistically significant relationship between reading culture and mental well-being, and hypothesis two shows a significant and positive relationship between library usage and the mental well-being of students. Congruently, hypothesis three shows a significant joint effect of reading culture and library usage on the mental well-being of students. Based on these findings, this study recommends that the management of Lagos State University should integrate reading culture into the curriculum, emphasizing its importance for both academic and leisure purposes. This can be achieved through initiatives like reading challenges and book clubs. Also, the management of the University should ensure that libraries become supportive environments by increasing study spaces, quiet zones, and diverse learning resources to accommodate various student preferences and needs.